Vacuum-Stabilized Palmar Cooling Mobilizes Circulating Small Pluripotent Stem Cells in Humans - DC, Torbjörn Ogéus; PgD; MSc; ScA; Riegner, Manuel; MD (Archives of Clinical and Biomedical Research, 2026)
Background: Small Pluripotent Stem Cells (SPSCs) have been identified in adult peripheral blood and are characterized by their small size and expression of pluripotency-associated markers. Strategies that safely and reproducibly increase the availability of such cells without pharmacological intervention remain of interest for translational and regenerative applications. Methods: In this paired pre–post observational study, 50 adult subjects (male and female, aged 20–67 years) underwent exposure to a standardized vacuum-based physiological stimulus using the Vacuul device. Peripheral blood samples were collected immediately before and after exposure. SPSCs were isolated using a size- and centrifugation-based enrichment protocol implemented within a standardized analytical framework. Cell concentration and viability were assessed using an automated cell counter, and immunocytochemical analyses were performed to evaluate expression of OCT4, SOX2, and SSEA-4, with Hoechst nuclear staining. Results: Baseline SPSC concentration averaged approximately 20 × 10? cells/mL. Following Vacuul exposure, SPSC concentration increased by a mean of approximately 30%, with individual responses ranging from 12% to 55%. All subjects demonstrated an increase in circulating SPSC concentration. Cell viability remained stable at 98–99% before and after exposure. Immunocytochemical analysis demonstrated preserved expression of pluripotency-associated markers and consistent nuclear staining following Vacuul exposure. Conclusions: Vacuum-Stabilized Palmar Cooling is associated with a reproducible increase in circulating SPSCs without compromising cell viability or altering pluripotency-associated marker expression.